2019
DOI: 10.3389/fmats.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Techniques for the Segmentation of Tomographic Image Data of Functional Materials

Abstract: In this paper, various kinds of applications are presented, in which tomographic image data depicting microstructures of materials are semantically segmented by combining machine learning methods and conventional image processing steps. The main focus of this paper is the grain-wise segmentation of time-resolved CT data of an AlCu specimen which was obtained in between several Ostwald ripening steps. The poorly visible grain boundaries in 3D CT data were enhanced using convolutional neural networks (CNNs). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 38 publications
0
64
0
Order By: Relevance
“…Naturally, these techniques have also been applied to analyze and extract information from the reconstructed datasets. For instance, neural networks and random forests have both been employed to solve the segmentation problem, wherein each pixel is assigned to a particular phase [124,125]; evolutionary algorithms have also been used to solve the alignment problem associated with interrupted in situ scans, including DCT [126,127]; finally, deep learning has demonstrated success in detecting key features and tracking their evolution over time [128][129][130]. These examples represent only the tip of the iceberg.…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…Naturally, these techniques have also been applied to analyze and extract information from the reconstructed datasets. For instance, neural networks and random forests have both been employed to solve the segmentation problem, wherein each pixel is assigned to a particular phase [124,125]; evolutionary algorithms have also been used to solve the alignment problem associated with interrupted in situ scans, including DCT [126,127]; finally, deep learning has demonstrated success in detecting key features and tracking their evolution over time [128][129][130]. These examples represent only the tip of the iceberg.…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…However, the methods of statistical learning, in particular CNNs, provide a promising technique with regard to automated image analysis. 2016; Petrich et al, 2017;Rivenson et al, 2017;Furat et al, 2019). 6.…”
Section: Cnn-empowered Crossover Detectionmentioning
confidence: 99%
“…Due to its fully convolutional nature, the input and output sizes of the network are arbitrary. 2016; Petrich et al, 2017;Rivenson et al, 2017;Furat et al, 2019). Integrating these techniques into the analysis process of fibril images is a promising approach that could drastically reduce the efforts needed to process these images using completely interactive approaches alone.…”
Section: Cnn-empowered Crossover Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Chowdhury et al used DL for the recognition of dendritic morphologies, [17] and Furat et al showed the application of CNNs for grain-wise segmentation of 3D CT data on Al-Cu alloy. [18] In this study, we investigate the 3D microstructure of an AlSi 12 CuMgNi alloy reinforced with 7%vol of Al 2 O 3 -Saffil short fibers and 15%vol of SiC particles. We show the application of an advanced DL method for the semantic segmentation of all phases present in this multiphase material.…”
mentioning
confidence: 99%